If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3a + -3f)(3a + 2f) = 0 Multiply (3a + -3f) * (3a + 2f) (3a * (3a + 2f) + -3f * (3a + 2f)) = 0 ((3a * 3a + 2f * 3a) + -3f * (3a + 2f)) = 0 Reorder the terms: ((6af + 9a2) + -3f * (3a + 2f)) = 0 ((6af + 9a2) + -3f * (3a + 2f)) = 0 (6af + 9a2 + (3a * -3f + 2f * -3f)) = 0 (6af + 9a2 + (-9af + -6f2)) = 0 Reorder the terms: (6af + -9af + 9a2 + -6f2) = 0 Combine like terms: 6af + -9af = -3af (-3af + 9a2 + -6f2) = 0 Solving -3af + 9a2 + -6f2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '3'. 3(-1af + 3a2 + -2f2) = 0 Factor a trinomial. 3((a + -1f)(3a + 2f)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(a + -1f)' equal to zero and attempt to solve: Simplifying a + -1f = 0 Solving a + -1f = 0 Move all terms containing a to the left, all other terms to the right. Add 'f' to each side of the equation. a + -1f + f = 0 + f Combine like terms: -1f + f = 0 a + 0 = 0 + f a = 0 + f Remove the zero: a = f Simplifying a = fSubproblem 2
Set the factor '(3a + 2f)' equal to zero and attempt to solve: Simplifying 3a + 2f = 0 Solving 3a + 2f = 0 Move all terms containing a to the left, all other terms to the right. Add '-2f' to each side of the equation. 3a + 2f + -2f = 0 + -2f Combine like terms: 2f + -2f = 0 3a + 0 = 0 + -2f 3a = 0 + -2f Remove the zero: 3a = -2f Divide each side by '3'. a = -0.6666666667f Simplifying a = -0.6666666667fSolution
a = {f, -0.6666666667f}
| 8y+5=8y-5 | | 15r=8r-56 | | 11-(6v+7)=-6v-4 | | 3x+12=5t+6 | | 6+3t=3t-14 | | -8-6(x+3)=2x-6x+5 | | -10-5x=10-10 | | 3x+16=32 | | 8(x+2)=40 | | -4+7(1-3m)=0 | | -y+2x=9 | | 3(x+2)=-x+30 | | [9(x+5)-7]+[4(x-12)+9]= | | 2.3x-0.11=0.8x+34.39 | | 3x-2(12)=-13 | | 3x-8=13-4p | | 5(2x-9)=7x-60 | | -9k+8k=0 | | 8.3x-25=4.9x+97.9 | | -1(y-8)=2(y+4) | | (30-2y)+3=y | | 3(y-2x)=2 | | 0.58+0.15y=4.78 | | 3(x-4)=y+5 | | 3+0.15x=4.78 | | 0.58-0.15x=4.78 | | =(2b+1)(2b-1) | | 5(5+y)=10x | | 0.7= | | -3n+9=6n-9 | | 22+4.1x=2x+32.6 | | 7d+d+-4d-7=5d |